Response to Intervention, and Special Education Directors' Characteristics - Bently, Gayla Ulm (My University, 2016)
Abstract: The topic of this dissertation was the factors that contribute to disproportionate representation of minority students in special education programs. The problem that motivated this study was that achievement gaps, high drop-out rates, low graduation rates, discipline occurrences, and low student retention rates plague students who are served in special education, and that African American students are disproportionately placed in special education programs. However, the reasons for the disproportionate representation of minority students in special education programs are unclear. Therefore, the purpose of this study was to examine special education directors’ leadership role characteristics such as (a) tenure as special education program director, (b) gender, (c) years of experience in education, (d) race or ethnicity, and (e) level of implementation of response-to-intervention (RTI) to determine how those factors impact district disproportionality for minority students in Georgia. A total of 155 of the 180 district-level Special Education Directors in the State of Georgia participated in this study. The results showed that the demographic and background characteristics of the Special Education Directors and the level of RTI were not related to disproportionality. Based on these results, it was recommended that future researchers should replicate this study in other geographic areas, should develop more comprehensive models of disproportionality, and should perform qualitative studies to develop a more comprehensive view of disproportionality.
Chapter I: INTRODUCTION1 | Statement of the Problem 5 | Purpose of the Study 6 | Research Questions 8 | Research Methodology 9 | Significance of the Study 11 | Theoretical Basis of the Study 12 | Limitations of the Study 13 | Definition of Terms 14 | Organization of the Study 17 | Chapter II: REVIEW OF RELATED LITERATURE 19 | Historical Perspective of Special Education 19 | Disproportionality in Special Education 24 | Leadership Gender Differences 41 | Leadership Induction and Stability 49 | Importance of Development Programs/Academies 57 | Summary 58 | Chapter III: RESEARCH DESIGN AND METHODOLOGY 59 | Research Design 59 | Participants 60 | Instrumentation 61 | Data Analysis 70 | Statistical Assumptions 72 | Summary 73 | Chapter IV: RESULTS 75 | Preliminary Analyses 76 | Results by Question 82 | Summary of Findings 108 | Chapter V: SUMMARY AND DISCUSSION 110 | Overview of the Study 110 | Methods 111 | Participants 112 | Variables Studied 112 | Procedures 113 | Summary of Findings 114 | Discussion of Findings 116 | Limitations of the Study 119 | Recommendations for Future Research 120 | Conclusions 121 | REFERENCES 123 | APPENDIX A: Survey 136 |
Keywords: Educational Leadership; Dissertation